Programa Ensino Integral (PEI): Uma análise das implicações para as condições do trabalho docente - VICTOR COQUEIRO DE SOUSA (2024)
In recent years, a full-time school program known in Portuguese as the “Programa Ensino Integral (PEI)” has become the central focus of educational public policies in the State of São Paulo. The guidelines and documents of the PEI promise an enhanced teaching career, with higher salaries, more time for lesson preparation, continuous training, and exclusive dedication to a single school. Based on these premises, this research examines the PEI, focusing on understanding the factors that influence its implementation regarding teacher training and work in São Paulo's education system. To achieve this, the study aimed to analyze its historical roots and, through a literature review and document analysis, identify potential discourses present in the documents related to the working conditions of teachers involved in the program. The research is grounded in the hypothesis that there is a process of precarization of teaching work, and it seeks to confirm this hypothesis within the PEI, which constitutes its primary objective. The adopted methodology follows a qualitative approach, with an emphasis on Document and Content Analysis. For the historical analysis, the research employed a method of source interpretation known as Document Analysis, with historical sources retrieved from the archives of the newspaper O Estado de S. Paulo and the Legislative Assembly of the State of São Paulo (ALESP), all related to the research subject. As for the Document and Content Analysis focused on teaching work, the guiding and training documents of the PEI (2014-2023), available on the website of the School of Training and Development of Education Professionals of the State of São Paulo (EFAPE), were analyzed. The research results indicate that there has indeed been a historical process of the precarization of teaching work in the State of São Paulo, which has been intensified with the advent of the PEI. The corporate and neoliberal management model adopted by the program has contributed to exacerbating this precarization, in line with the public educational policies implemented in the state.